Finding rigorous thermodynamic model parameters for the simulation of a reactive distillation column: case of ETBE production - Durruty, Gisela N. (2014)
A model for a reactive distillation column for ETBE production was devel-oped using both a rigorous thermodynamic model (UNIFAC) and hydraulic constrains. The thermodynamic model included an activity coefficient approach for the liquid phase, UNIFAC, and ideal gas approximation for the vapor phase. The binary interaction parameters of UNIFAC were improved to better predict the equilibrium in the column. The binary interaction parameters were estimat-ed using experimental data taken from literature.